Value assessment strategies and return on investment of the twenty-first century libraries: Covenant University in view (2018)
Academics expect the libraries to support and promote leading-edge learning, teaching, and research, just as parents and students expect enhancement of students’ collegiate experience among others while stakeholders count on academic libraries to achieve goals of the institution. As a result of the cost of running and sustaining an academic library, there is need for justification of return on investment, which can be determined only by its relevance and value. Thus, libraries are required to demonstrate evidence that they can and are achieving set goals. This chapter presents how Centre for Learning Resources (academic library) Covenant University, Ota, Nigeria, has successfully demonstrated its return on investment, worth, and value to its host community, users and stakeholders.